List of the birds from Faculty of Agronomy of Santa Rosa (La Pampa) and its surrounding (Semiárida, 2020)
This work, is the result 01 a study made of birds in the Faculty of Agronomy of Santa Rosa and its surrounding. The observations were made during the period between 1995/1999. Have been added data about the Poblacional State and ecological habit 01 birds. 89 species belonging to 27 families have been recorded. 67 percent is permanent resident. The communities are composed mainly by "scarce" species. During the period of the study 31 species breed in the area. We recorded Molothrus bonarinesis as parasite.
Keywords: Birds; nesting; La Pampa residence